Energia renovável e desenvolvimento: uma abordagem econômica e social - Mentone, Fernando Augusto (2015)
The objective of this paper is to evaluate the existence of the relationship between renewable energy generation and the Human Development Index (HDI) in short and long terms, based on methodology previously proposed and excluding from the analysis the economic effects generated by the energy production itself. The results indicate that the relationship between the variables exists, but there are different effects between the groups of countries in short and long term, suggesting that governments strategically adopt energy policies with different assumptions